Marketing strategies of chosen polish cement factories in the backrground of construction sector development - Kowalik, J. (Видавництво Львівської політехніки, 2013)
The construction sector is a very important branch of economy, substantially influencing its development. In the recent years one can observe a high dynamism of this sector's development in Poland, determined mainly by infrastructure development connected with organizing Euro 2012, as well as construction projects realized by local governments and financed by the European Union. The article presents the analysis of the cement trade in Poland accompanied by the changes occurring in the construction sector. The paper also discusses marketing strategies realized for several years by chosen cement factories operating on Polish market. Будівельний сектор є важливою галуззю економіки, яка істотно впливає на її розвиток. В останні роки спостерігається висока динаміка розвитку цього сектору в Польщі, що переважно визначається розвитком інфраструктури, пов'язаним із організацією Євро-2012, а також будівельними проектами, що реалізуються органами місцевого самоврядування і фінансуються Європейським Союзом. Проаналізована торгівля цементом у Польщі, що супроводжується змінами, які відбуваються у будівельному секторі. Обговорюються маркетингові стратегії, реалізовані протягом кількох років на різних цементних заводах, що функціонують на польському ринку.
Маркетингові стратегії на вибраних польських цементних заводах на фоні розвитку будівельного сектору
Keywords: construction sector; marketing strategies; cement factories in Poland; будівельний сектор; маркетингові стратегії; цементні заводи у Польщі